The Influence of Marriage Communication Skills and Sexual Satisfaction on the Marriage Quality of Female Nurses at Mental Hospital - Sanjaya, Ersa Lanang; Putra, Muhammad Ghazali Bagus Ani (Makara Human Behavior Studies in Asia, 2021)
This research aims to investigate the influence of marriage communication skills and sexual satisfaction on the marriage quality of female nurses who work at a mental hospital and whose husbands also work. Working females, especially those who work in shifts, have less time to spend with their families and spouse, which, in turn prove to be great challenges to building a good relationship between partners. Our principal instrument of data collection is questionnaires. 108 female nurses who work at Dr. Radjiman Wediodiningrat Mental Hospital and have working husbands participated on this study. The results of the multiple regression analysis demonstrated that marriage communication skills and sexual satisfaction can influence marriage quality. This finding suggests that the marriage communication skills variable and the sexual satisfaction variable exert 58.1% influence on the marriage quality variable, while the remaining 41.9% influence is exerted by other variables. These findings are expected to support our recommendation for employing institutions to reconsider the distribution of their employees’ working hours, so that each individual can spend more time with their families. Besides that, every couple must proactively find the best way to maintain their marriage quality by taking into account communication quality and sexual satisfaction factors.